عناصر و مناهج التنمية البشرية في الاقتصاد الإسلامي كنموذج للرفاه الاقتصادي - عمر بابكر, د/ محمد أحمد (Sciences humaines, 2016)
This research deals with human development concept which we substitute with Quranic concept , that is the concept of good life . Important of this research manifests in drawing attention to the existence of terms that are more suitable for Muslims in terms of concept and their view to the hereafter . The research supposes that the concept of good life is more deep and better than other concepts , because of its consistence of  both times - hereafter and thereafter and by bringing together sole and matter . The research followed the deductive and analytical methodologies . The research composes of an introduction and three sections . First one deals with the concept of human development in Islamic perspective , while the second deals with the components and principles of human development in Islamic perspective . The third explains the concept of good life as a model of human development . Key Concepts : Human development , A'afia (good health) , good life , good deed , Zuhd.       يعالج هذا البحث موضوع التنمية البشرية من حيث المفهوم والذى يستبدله بمفهوم قرآنى هو مفهوم الحياة الطيبة . تبرز أهمية هذا البحث فى التنبيه على وجود مصطلحات أكثر ملائمة للمسلمين من حيث المفهوم والنظر إلى الدنيا . ويفترض أن مفهوم الحياة الطيبة أعمق   من غيره وأفضل لشموله أمد الدارين وجمعه بين الروح والمادة . اتبع البحث المنهج الاستنباطى والمنهج التحليلى . ويتكون البحث من : مقدمة وثلاثة مباحث . يتناول الأول مفهوم التنمية البشرية    من المنظور الإسلامى , ويعالج الثانى عناصر ومبادئ التنمية البشرية          من المنظور الإسلامى , ويبين الثالث مفهوم الحياة الطيبة كنموذج للتنمية البشرية . الكلمات الإرشادية : التنمية البشرية, العافية الحياة الطيبة, الحسنة, الزهد.